Spontaneous pregnancy rate after saline infusion sonogram treat done under high pressure - Elsharkawy, Suzan Samir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Failure to achieve conception after 12 months of regular unprotected intercourse is defined as infertility. The aim of this study was evaluating SIS done under high pressure (SIStreat) as a treatment procedure, for relieving simple tubal obstruction and on cumulative pregnancy rate in infertile women. Methods: A prospective, interventional trial was done (October 2017 - November 2018) on 106 eligible women. All patients performed SIS. Patient with tubes patent under low pressure were assigned as control group, the rest of them were subjected to SIStreat, this group was farther divided into Group 2-a (patent under high pressure) and Group 2-b (occluded under high pressure). All patients had regular intercourse for 6 months. Pregnancy was confirmed by serum B-HCG. Results: we compared patients who performed conventional SIS (n = 100 cases) to patients who performed SIStreat afterwards (n = 84) according to the number of patent tubes. There was a high statistically significant difference in favor of SIStreat group (p < 0.001). Also, there was no significant difference in pregnancy rate between control group 62.5% and Group 2-a 45.7% (p = 0.226). Conclusions: SIStreat is a whole new procedure for opening fallopian tubes (diagnosed occluded by SIS). Patients who were successfully treated by SIStreat had cumulative pregnancy rate comparable to patients who were diagnosed to have patent tubes using conventional SIS.